Gerak Politik Uang Pada Pilkada Dumai 2020: Sarana Pendidikan Politik Yang Baik Bagi Mahasiswa Di Perguruan Tinggi Se-Kota Dumai - Hafrida, Lis (Metta : Jurnal Ilmu Multidisiplin, 2021)
This research was a qualitative descriptive study, aimed at describing the application of political education received by students on campus to money politics that occurred in the Election of Mayor and Deputy Mayor at Dumai in 2020. The instrument used a questionnaire developing Guttman scale. Its population was all students who are enrolled in universities throughout Dumai. Respondents amounted to 760 people who were selected by incidental sampling technique. Some findings of this study were: (1) A total of 74.7% of students in the city of Dumai knew about money politics; (2) 71.7% of respondents knww the purpose of money politics; (3) 79.9% of respondents had experience of receiving money from the success team and/or pairs of candidates; (4) A total of 78.9% of student respondents already knew the impact of money politics on the 2020 Dumai Mayor and Deputy Mayor Election; (5) A total of 73.6% of respondents had experience receiving money from unscrupulous pairs of candidates during the previous election when the previous election was held; (5) Questions regarding the prediction of money politics during the election was 85% of respondents answered that it would not happen; (6) The statement of the respondent's attitude when receiving money and choosing the candidate pair in question would be made by 22.1% of the respondents; and (7) A total of 71.4% of respondents did not accept the money given and did not choose the candidate pair. In conclusion, from the percentage of the data above, realization of political education received by the students in some campus in Dumai with the attitude towards the rejection of money politics in happened in Dumai on 2020 Mayor election is better.